INCREASING THE PRODUCTIVITY OF ACTIVE AGEING-BASED ELDERLY IN OVERCOMING PHYSICAL PROBLEMS THROUGH GYMNASTICS - Vadesma, Iwanda Theza; Rajagukguk, Aranssa Dwiveronikca; Aprilia, Nadia; Setiawan, Irvan; Setyomurti, Mikha Anggitama; Rahadhini, Marjam Desma (EMPOWERING HUMANITY, 2023)
Aging is a natural process for people aged 60 years and above. Physical and mental decline is the process of aging. Therefore, the PKM-PM team of Slamet Riyadi University Surakarta conducted guided activities through physical gymnastics and brain exercises. The purpose of this service is to help increase the productivity of the elderly through active ageing at Widhi Asih Surakarta Nursing Home. The problem-solving approach in the PKM program is training and guidance on active ageing, especially physical gymnastics and brain exercises. After this empowerment event, it is hoped that the elderly at Panti Wreda Widhi Asih Surakarta can be empowered to age actively and become creative, healthy and happy elderly.